Pendidikan Menurut Perspektif Ustadz Adi Hidayat dan Buya Yahya - Septia Fahiroh; Muthi’ah Muthi'ah; Rahma Yesi; Febi Amanda Kurnia; Alihan Satra; Syarnubi, Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
Education in Islam plays a central role in shaping human character and morals. Two well-known figures in the community, namely contemporary scholars Ustadz Adi Hidayat and Buya Yahya, have distinctive views on the concept of Islamic education. This article aims to analyze the perspectives of the two scholars regarding the concept of education in Islam, the purpose of education, the difference with general education, moral and character education, and its relevance in modern life which relates it to the application of technology. The method in this research is a literature study by analyzing lectures, books, and scientific studies that they convey. The results of this study illustrate that Ustadz Adi Hidayat emphasizes the importance of Qur'an and science-based education as an effort to build a generation of intellectuals with morals. On the other hand, Buya Yahya is more inclined to the exemplary aspect of learning and instilling adab before knowledge. These two approaches complement each other and provide a comprehensive insight into how Islamic education can be optimally applied in everyday life.